2011
DOI: 10.1111/j.1540-8183.2011.00666.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Angio-Guided Complete Revascularization versus Culprit Vessel PCI Followed by Ischemia-Guided Staged PCI in STEMI Patients with Multivessel Disease

Abstract: Early complete revascularization based only on angiographic findings in patients with STEMI and MVD is associated with an excess of periprocedural/re-MI and with a significantly higher incidence of MACE at follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…In addition, another reasonable explanation would be the fact that the inflammatory reaction triggered during the ACS process responsible for the plaque instability in STEMI was not limited to the culprit lesion, consequently compromising the entire coronary tree [ 23 ] . Although it did not occur in our sample, Meliga et al [ 36 ] reported that the complete revascularization of these patients should not be based only on angiographic findings but ideally should be guided by evidence of correlated ischemia, as justified by the high risk of periprocedural ischemic complications.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, another reasonable explanation would be the fact that the inflammatory reaction triggered during the ACS process responsible for the plaque instability in STEMI was not limited to the culprit lesion, consequently compromising the entire coronary tree [ 23 ] . Although it did not occur in our sample, Meliga et al [ 36 ] reported that the complete revascularization of these patients should not be based only on angiographic findings but ideally should be guided by evidence of correlated ischemia, as justified by the high risk of periprocedural ischemic complications.…”
Section: Discussionmentioning
confidence: 76%
“…(2) It could provide a better appraisal of the revascularization strategy, including avoiding unnecessary stenting when the residual stenosis is not deemed significant . (3) In STEMI case, the repeated angiogram may allow treatment of a nonculprit artery in patients with multivessel disease . However, the disadvantages of deferred‐stenting strategy with higher costs, prolonged hospitalization, and the risk of reocclusion should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…CR was defined as the absence of total occlusion, with no residual stenosis of >70% found in any major coronary artery or major branch, at discharge, based on visual assessment [15,16]. To validate the visual assessment, quantitative coronary angiography (QCA) was performed in 254 lesions and compared with visual assessment; there was no significant difference between the two methods (P = 0.41, data not shown).…”
Section: Methodsmentioning
confidence: 99%